Teacher Training in Intercultural Education: Teacher Perceptions - Victoria Figueredo-Canosa; Luis Ortiz Jiménez; Cristina Sánchez Romero; María Carmen López Berlanga (MDPI AG, 2020)
Background: The aim of the present study was to evaluate teacher perceptions on the training received in intercultural education. Methods: The article presents a quantitative, non- experimental and ex-post-facto type of research; directed to inquire about the perceptions of the teachers of primary education in Andalusia (Spain) in relation to the intercultural training received. Based on the descriptive survey method, two questionnaires were administered to a sample composed of 320 students and 80 teachers. Results: The results show certain strengths of the training teacher programs in the field of interculturality (encouragement of reflection, participation and collaboration …), as well as weaknesses (decontextualization, inflexibility, primacy of theoretical learning, non-transversal character, etc.). Conclusions: Despite strengths, intercultural teacher training continues to be a challenge in Andalusia.